The Influence of Supply Chain Integration on Supply Chain Performance in Private Firms of Bangkok: Moderating Role of Leadership - Khasasin, Rungarun (ExcelingTech, 2020)
The performance of the supply chain is the necessary element for the success of the organization because it improves the business processes that could improve the business performance and also gain the intention of the regulators and researcher nowadays. Thus, present article aims to analyze the impact of supply chain integration such as internal integration, information integration and customer integration on the supply chain performance of the private firms in Bangkok, Thailand. The investigation of the moderating role of leadership among the nexus of supply chain integration and supply chain performance is also part of the purpose of the current study. The employees of private firms that are dealing with the process of the supply chain are the respondents from whom data has been gathered by using survey questionnaires. The effective statistical tool has been used for analysis purpose named as smart-PLS. The results indicated that positive along with significant association among the nexus of all the supply chain integrations and supply chain performance. The findings also exposed that the leadership has been significantly moderated among the nexus of supply chain information integration, supply chain customer integration and supply chain performance. These outcomes are suitable for the regulators who want to develop the regulations related to the performance of the supply chain that could increase the performance of the organization.